Low-temperature cordierite ceramics with porous structure for thermal shock resistance products - Olena Khomenko; Aleksandr Zaichuk; Aleksandra Amelina (Open Ceramics, 2024)
This article shows the results of the study of low-temperature (1100−1150 °C) porous ceramics of cordierite composition. The technological manufacturing parameters, the features of the microstructural and phase composition of ceramics have been studied. A decrease in the sintering temperature is achieved by appending a part of components using eutectic glass of MgO–Al2O3–SiO2 pseudoternary system. The principle of reactive formation of the structure of the ceramic sample is implemented in the process of its low-temperature firing. The formation of α-cordierite occurs in the process of firing ceramics by means of intensive interaction between eutectic glass components and crystalline fillers, as well as in the result of glass crystallization. By means of the thin layers of the glassy phase, cordierite crystals form a hard base with a branched system of interconnected open pores (30.0−31.3 %). The cordierite-phase crystals, forming the structure of ceramics, have a particle size ranging from 0.2 to 0.3 μm to 1.0−2.0 μm. The specific surface area of the porous cordierite ceramics is in the range of 4.2–4.7 m2/g. The developed cordierite ceramics is characterized by its low coefficient of linear temperature expansion (1.7–2.6)·10−6 °С−1, which determines its high thermal shock resistance (1000−1150°С). The ceramics may be used as filtering elements in high-temperature filtering units, as well as catalyst carriers in the exhaust systems of combustion engines for discharging the sooty component.